Inhibition of Glucose-Stimulated Insulin Secretion by KCNJ15, a Newly Identified Susceptibility Gene for Type 2 Diabetes - Okamoto, Koji (American Diabetes Association, 2012)
Potassium inwardly rectifying channel, subfamily J, member 15 (KCNJ15) is a type 2 diabetes–associated risk gene, and Kcnj15 overexpression suppresses insulin secretion in rat insulinoma (INS1) cells. The aim of the current study was to characterize the role of Kcnj15 by knockdown of this gene in vitro and in vivo. Human islet cells were used to determine the expression of KCNJ15. Expression of KCNJ15 mRNA in islets was higher in subjects with type 2 diabetes. In INS1 cells, Kcnj15 expression was induced by high glucose–containing medium. Regulation of Kcnj15 by glucose and its effect on insulin secretion were analyzed in INS1 cells and in normal mice and diabetic mice by the inactivation of Kcnj15 using small interfering RNA. Knockdown of Kcnj15 increased the insulin secretion in vitro and in vivo. KCNJ15 and Ca(2+)-sensing receptor (CsR) interact in the kidney. Binding of Kcnj15 with CsR was also detected in INS1 cells. In conclusion, downregulation of Kcnj15 leads to increased insulin secretion in vitro and in vivo. The mechanism to regulate insulin secretion involves KCNJ15 and CsR.